2015
DOI: 10.1002/jwmg.910
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of great gray owl nest sites and nesting habitats in California

Abstract: The great gray owl (Strix nebulosa) is listed by the state of California as endangered, with a population estimate of fewer than 300 individuals in the state. Nest‐site availability has been suggested as a limiting factor for population growth in California, but information on nest types and nesting habitat has been based on a small number of nests that may not fully represent the variety of conditions used by the species. We collated all known nesting records in the Sierra Nevada mountains of California since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Great Gray Owl nests were typically surrounded by dense forest (.60% canopy closure), consistent with findings from elsewhere in California (Greene 1995, Wu et al 2015, Oregon (Bull and Henjum 1990), and eastern Idaho and northwest Wyoming (Whitfield and Gaffney 1997). More surprising was that the forests in a 900-m radius around nests contained large areas (109-204 ha) dominated by small-diameter trees (25.4-50.6 cm), whereas other research in California, based primarily on mid-elevation nest sites, has emphasized the importance of large trees in mid-to late-seral nest stands (Winter 1986, Sears 2006, Wu et al 2015. In northeastern Oregon, Bull and Henjum (1990) found Great Gray Owls nesting in large trees in relatively late-seral stands, whereas in southwestern Oregon, areas around Great Gray Owl nests were characterized by a high number of small trees and low densities of large trees (Fetz et al 2003), similar to what we observed at our study site.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Great Gray Owl nests were typically surrounded by dense forest (.60% canopy closure), consistent with findings from elsewhere in California (Greene 1995, Wu et al 2015, Oregon (Bull and Henjum 1990), and eastern Idaho and northwest Wyoming (Whitfield and Gaffney 1997). More surprising was that the forests in a 900-m radius around nests contained large areas (109-204 ha) dominated by small-diameter trees (25.4-50.6 cm), whereas other research in California, based primarily on mid-elevation nest sites, has emphasized the importance of large trees in mid-to late-seral nest stands (Winter 1986, Sears 2006, Wu et al 2015. In northeastern Oregon, Bull and Henjum (1990) found Great Gray Owls nesting in large trees in relatively late-seral stands, whereas in southwestern Oregon, areas around Great Gray Owl nests were characterized by a high number of small trees and low densities of large trees (Fetz et al 2003), similar to what we observed at our study site.…”
Section: Discussionsupporting
confidence: 73%
“…Half of the nesting territories had 70-89% conifer cover and 8-30% hardwood cover, whereas the remaining sites had 8-60% conifer and 20-71% hardwood cover. The average percent cover of hardwood across the eight sites in our study area was higher than around Great Gray Owl nests elsewhere in California (Wu et al 2015), reflecting the overall greater abundance of oak trees in lower-montane forests of the Sierra Nevada than at higher elevations. Great Gray Owl nests were typically surrounded by dense forest (.60% canopy closure), consistent with findings from elsewhere in California (Greene 1995, Wu et al 2015, Oregon (Bull and Henjum 1990), and eastern Idaho and northwest Wyoming (Whitfield and Gaffney 1997).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations